RESPON PERTUMBUHAN TANAMAN KANGKUNG (Ipomoea reptans Poir) PADA PERLAKUAN JUMLAH BENIH DAN NUTRISI DENGAN SYSTEM HIDROPONIK SUMBU DI WILAYAH PESISIR - Sajuri Sajuri; Hasna Darin Mawaripta; Eka Adi Supriyanto; Syakiroh Jazilah (Percetakan Umi Toaha Makassar, 2022)
Hydroponics is a farming system that uses no soil but uses water that is nourished as a food source for plants. This study aims to determine the effect of the number of seeds and concentration of nutrients on the growth of water spinach (Ipomoea reptans poir). The study was conducted at the Slamaran Experimental Garden, Pekalongan, Central Java. The experimental design used was a randomized block design with the treatment being tried being the number of seeds per hole (1 seed per hole, 2 seeds per hole, and 3 seeds per hole) and nutrient concentration (0 ppm, 500 ppm, 1000 ppm, 1500 ppm).The observed variables were plant height, stem diameter, number of leaves, leaf area, longest root length, stover wet weight, plant wet weight, plant growth rate, relative growth rate, and volume of water absorbed. The data analysis used is the F Test, and if there is a real difference, then proceed with the smallest real difference test of 5%. The results showed that the number of seeds differed significantly to very significantly with respect to all observed variables except the longest leaf area and root length variables. The best treatments are 1 seed per hole and 3 seeds per hole. All observed variables were significantly affected by the treatment of different nutrient concentrations. The best nutrient concentration is achieved at 1500 ppm. Interaction occurs between the number of seeds per hole with nutrient concentration on the variable number of leaves, plant wet weight, plant growth rate, relative growth rate, and volume of water absorbed.